Most common diseases and disorders of the breast in children and young women - Jakubik, Jarosław (Contemporary Oncology/Współczesna Onkologia, 2004)
Incidence of breast diseases increases with age. In children and adolescent women, breast diseases are not frequent. Pain, i.e. mastalgia, inflammations and developmental disorders are among them. Benign neoplasms are encountered less often. Cancers in patients below the age of 20 are extremely rare. In Polish literature, problems concerning breast tumors are rarely discussed. No univocal standards of treatment of breast diseases in children have been created. On the basis of medical literature and the author’s own research, the author describes and discusses issues of normal development of breast as well as developmental abnormalities encountered in clinical practice. The author describes also the material of breast tumors diagnosed at young age and removed surgically. The most common benign tumor is fibroadenoma; its special form occurring mostly at young age is juvenile fibroadenoma. Benign dysplasia of breast and juvenile papillomatosis are described in detail. Characteristic features of rare tumors as well as cyclic mastalgia and cyclic nodularity are also discussed. Treatment of breast neoplasms of young women is similar to that of older women.